Characterization of crystalline phases of bone ash - Ahsan, M; Dewan, AH; Mustafi, S; Ahmed, S (Bangladesh Journal of Scientific and Industrial Research, 2012)
Bone ash has been prepared from waste cattle bone choosing two different calcination temperatures (1050°C and 1100°C). The heat treatment was performed by conducting quenching and without quenching techniques. The prepared bone ash was characterized using XRF, XRD and FTIR techniques which revealed that the observed data were in excellent agreement with the standard values for hydroxyapatite (the prime raw material of bone china) and could be used as the raw material for bone china ceramic ware. DOI: http://dx.doi.org/10.3329/bjsir.v47i3.13057 Bangladesh J. Sci. Ind. Res. 47(3), 265-268, 2012